2020
DOI: 10.1007/s00200-020-00427-x
|View full text |Cite
|
Sign up to set email alerts
|

HELP: a sparse error locator polynomial for BCH codes

Abstract: In 1990 Cooper suggested to use Groebner bases' computations to decode cyclic codes and his idea gave rise to many research papers. In particular, as proved by Sala-Orsini, once defined the polynomial ring whose variables are the syndromes, the locations and the error values and considered the syndrome ideal, only one polynomial of a lexicographical Groebner basis for such ideal is necessary to decode (the general error locator polynomial, a.k.a. GELP). The decoding procedure only consists in evaluating this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Experiments showed that in that setting HELP has a very sparse formula, which has been proved in [12]:…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Experiments showed that in that setting HELP has a very sparse formula, which has been proved in [12]:…”
Section: Introductionmentioning
confidence: 94%
“…The shape of N 2 for a [2 m − 1, 2]-code C over F 2 m has been given recently by [12] which moreover proved that the related Gröbner basis has the shape G = (x n 1 − 1, g 2 , z 2 + z 1 + x 1 , g 4 ) where (see [37])…”
Section: The Error Varietymentioning
confidence: 99%
See 2 more Smart Citations